The sandpile group of a thick cycle graph - Diane Christine Alar; Jonathan Celaya; Luis David Garcia Puente; Micah Henson; Ashley K. Wheeler (Electronic Journal of Graph Theory and Applications (EJGTA), 2022)
The majority of graphs whose sandpile groups are known are either regular or simple. We give an explicit formula for a family of non-regular multi-graphs called thick cycles. A thick cycle graph is a cycle where multi-edges are permitted. Its sandpile group is the direct sum of cyclic groups of orders given by quotients of greatest common divisors of minors of its Laplacian matrix. We show these greatest common divisors can be expressed in terms of monomials in the graph’s edge multiplicities.